Efficacy of duodenal bulb biopsy for diagnosis of celiac disease: a systematic review and meta-analysis - McCarty, Thomas R.; O’Brien, Corey R.; Gremida, Anas; Ling, Christina; Rustagi, Tarun (Endoscopy International Open, 2018)
Background and study aims Although duodenal biopsy is considered the “gold standard” for diagnosis of celiac disease, the optimal location of biopsy within the small bowel for diagnosis remains unclear. The primary aim of this study was to perform a structured systematic review and meta-analysis to evaluate the diagnostic utility of endoscopic duodenal bulb biopsy for celiac disease.Patients and methods Searches of PubMed, EMBASE, Web of Science, and Cochrane Library databases were performed from 2000 through December 2017. Review of titles/abstracts, full review of potentially relevant studies, and data abstraction was performed. Measured outcomes of adult and pediatric patients included location of biopsy, mean number of biopsies performed, and diagnosis of celiac disease as defined by the modified Marsh-Oberhuber classification. Results A total of 17 studies (n = 4050) were included. Seven studies evaluated adults and 11 studies assessed pediatric populations. Mean age of adults and pediatric patients was 46.70 ± 2.69 and 6.33 ± 1.26 years, respectively. Overall, sampling from the duodenal bulb demonstrated a 5 % (95 % CI 3 – 9; P < 0.001) increase in the diagnostic yield of celiac disease. When stratified by pediatric and adult populations, duodenal bulb biopsy demonstrated a 4 % (95 % CI: 1 to 9; P < 0.001) and 8 % (95 % CI: 6 to 10; P < 0.001) increase in the diagnostic yield of celiac disease. Non-celiac histologic diagnoses including Brunner gland hyperplasia and peptic duodenitis were reported more commonly in the duodenal bulb as compared to the distal duodenum with an increase in diagnostic yield of 4 % (95 % CI 3 – 5; P < 0.001) and 1 % (95 % CI 1 – 2; P < 0.001), respectively.Conclusions Based upon our results, biopsy and histologic examination of duodenal bulb during routine upper endoscopy increases the diagnostic yield of celiac disease.